2021
DOI: 10.3389/fpsyg.2021.753463
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Flipped Learning Concerning Learning Motivation and Learning Attitude in Language Learning

Abstract: From the popularity of flipped teaching in United States primary and high schools, it is thought that students have more learning control to adjust to the learning progress and are assisted in problem solving and learning guidance during class period. It is believed that flipped teaching could prompt underachieving learners’ active learning and thereby enhance learning effectiveness. A total of 386 high school students in Chungli, Taiwan, were part of an experimental study and the research results are summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
1
12
1
1
Order By: Relevance
“…This could indicate that a flipped classroom could result in better class performance. This finding corroborates with the works of Chou et al (2021) and Mystica (2018) who found out that a flipped classrooms students demonstrated better comprehension levels with the teaching content due to the change in learning style and attitude and that flipped classrooms enhanced job satisfaction on the part of the teacher and students improved learning performance.…”
Section: B Differences In Class Performancesupporting
confidence: 90%
See 2 more Smart Citations
“…This could indicate that a flipped classroom could result in better class performance. This finding corroborates with the works of Chou et al (2021) and Mystica (2018) who found out that a flipped classrooms students demonstrated better comprehension levels with the teaching content due to the change in learning style and attitude and that flipped classrooms enhanced job satisfaction on the part of the teacher and students improved learning performance.…”
Section: B Differences In Class Performancesupporting
confidence: 90%
“…Some studies showed that students who participated in the flipped teaching models demonstrated better comprehension levels with the teaching content due to this change in learning style and attitude. This evidence suggested further developments regarding active learning ability and enhanced learning effectiveness, and the prompting of creativity resulting in a shift from passive learner to the active learner has been proposed (Chou et al, 2021).…”
Section: A Related Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Academic performance also increased and learning autonomy developed. In another study with 386 high school students, Chou et al (2021) concluded that learning effectiveness is enhanced by using FL in language classes. Many students in that study also considered that the teaching content was easier to assimilate.…”
Section: Advantages Of Flipped Learning Methodologymentioning
confidence: 99%
“…Flipped teaching may encourage underachieving students to study acting and improve their learning efficacy and psychological needs through self-determination theory. ( Chou et al, 2021 ; Chiu, 2022 ) studies examined student engagement in online learning and its effectson students learning outcomes. The study aims to determine if there is a strong correlation between e-learning and student motivation in higher education and the increasing use of e-learning ( Harandi, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%